Challenges and Opportunities for Integrating Preventive Substance-Use-Care Services in Primary Care through the Affordable Care Act - Udi E. Ghitza; Betty Tai (2014)
Undertreated or untreated substance use disorders (SUD) remain a pervasive, medically-harmful public health problem in the United States, particularly in medically underserved and low-income populations lacking access to appropriate treatment. The need for greater access to SUD treatment was expressed as policy in the Final Rule on standards related to essential health benefits, required to be covered through the 2010 Affordable Care Act (ACA) health insurance exchanges. SUD treatment services have been included as an essential health benefit, in a manner that complies with the Mental Health Parity and Addiction Equity Act (MHPAEA) of 2008. Consequently, with the ACA, a vast expansion of SUD-care services in primary care is looming. This commentary discusses challenges and opportunities under the ACA for equipping health care professionals with appropriate workforce training, infrastructure, and resources to support and guide science-based Screening, Brief Intervention, and Referral to Treatment (SBIRT) for SUD in primary care.